Evidência da transformação dinâmica de ferrita durante simulação termomecânica de um aço microligado X70 acima da temperatura Ae3 - Rodrigues, Maria Veronica Goncalves (2024)
It is known that strain-induced ferrite, known as dynamic transformation (DT), can occur in the austenite field above the Ae3 temperature in a rapidly displacive way and after diffusionally under stress. In this investigation, laboratory-scale physical simulation of tensile test in a customized Gleeble thermomechanical simulator system equipped with a synchrotron light X-ray beam (12 keV) was carried out on a linepipe steel at 50 o C above the Ae3. The X-ray diffraction (XRD) patterns confirmed the formation of ferrite inside the stable austenite field during strain. The results confirm the direct evidence of the onset of ferrite formation due to the applied strain and its increase into a higher volume fraction as the deformation continues to increase. The main ferritephase peaks detected by the in-situ XRD were (110) and (221). Both increased their intensity with the increasing strain, leading to a sharp decrease in the gamma-phase peaks (111) and (220) plane intensities. The total volume fraction of all ferrite peaks increased to approximately 50% when the strain reached a value of 0.3 while the fraction of all austenite peaks decreased proportionally. Microscopic measurements of the presented phases have shown an excellent agreement with the results obtained from direct XRD results, confirming that previous researchers have correctly calculated the number of dynamically transformed phases during thermomechanical processes. A comprehensive understanding of the DT phenomenon mechanism is important to help the industry sector design improved manufacturing schedules for final products with excellent quality and properties